Status and future of the Juelich CV28 compact cyclotron - Hölzle, R. (Вопросы атомной науки и техники, 2006)
The parameters of compact cyclotron with changeable energy CV28 and modernization of its systems and possible applications of the accelerated protons, deuterons, ³Не and alpha particles is described Приведены параметры компактного циклотрона CV28 с изменяемой энергией. Описаны модернизация его систем и возможные применения ускоряемых протонов, дейтронов, ³Не- и альфа-частиц. Приведені параметри компактного циклотрону CV28 із змінною енергією. Описані модернізація його систем і можливі застосування прискорюваних протонів, дейтронів, ³Не-і альфа-частинок.